Root and crown rot pathogens causing wilt symptoms on field-grown marijuana (Cannabis sativa L.) plants. Issue 4 (2nd October 2018) - Punja, Zamir K.; Scott, Cameron; Chen, Sarah
Abstract: Yellowing and wilting symptoms on field-grown Cannabis sativa (cannabis) plants followed by total plant collapse under conditions of extreme hot weather were observed in northern California in 2017. The crown regions of affected plants were dark and sunken and internal tissue discolouration extended 10–15 cm above the soil surface. Isolations made from the pith, vascular and cortical tissues in the crown region yielded Fusarium oxysporum (40% frequency), F. brachygibbosum (28% frequency), Pythium aphanidermatum (22% frequency), Fusarium solani and F. equiseti (5% frequency each). Pathogenicity tests were conducted on rooted plantlets to establish the extent of root and crown decay, as well as on mature stems to determine the extent of stem tissue colonization caused by these species. Extensive reduction in root length was caused by F. solani, F. oxysporum, F. brachygibbosum and P. aphanidermatum and wounding significantly enhanced disease development. Stem tissue colonization by these pathogens at wound sites was similarly extensive. Isolates of F. equiseti were non-pathogenic. Both F. solani and P. aphanidermatum caused plant mortality within 6–10 weeks following inoculation. In phylogenetic analyses using the internal transcribed spacer (ITS) rDNA region and the elongation factor 1 ( EF-1α ) region, F. oxysporum isolates from cannabis plants in northern California were grouped separately from all other formae speciales and from isolates previously recovered from British Columbia. Two isolates of F. brachygibbosum were identical to an isolate previously reported to infect almond stems in cold storage and field-grown seedlings in northern California. These findings indicate that a complex of pathogens potentially can cause root and crown rot under field conditions, resulting in wilt symptoms and collapse of cannabis plants.